2020
DOI: 10.1007/s40820-020-00536-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-Atom Cobalt-Based Electrochemical Biomimetic Uric Acid Sensor with Wide Linear Range and Ultralow Detection Limit

Abstract: Uric acid (UA) detection is essential in diagnosis of arthritis, preeclampsia, renal disorder, and cardiovascular diseases, but it is very challenging to realize the required wide detection range and low detection limit. We present here a single-atom catalyst consisting of Co(II) atoms coordinated by an average of 3.4 N atoms on an N-doped graphene matrix (A–Co–NG) to build an electrochemical biomimetic sensor for UA detection. The A–Co–NG sensor achieves a wide detection range over 0.4–41,950 μM and an extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 58 publications
0
59
0
Order By: Relevance
“…Research on graphene-based nanomaterials has boomed in biomaterial applications over the past few years. With outstanding physical, chemical and biological properties, graphene is considered to be revolutionary material and shows great potential for applications in tissue regeneration, drug delivery and other biomedical areas (Hu et al, 2020;Fu et al, 2021;Unal et al, 2021). Therefore, the purpose of this review is to highlight the scientific progress over the years and further summarize the physical and chemical properties, family members and applications in bone tissue engineering of this graphene-based nanomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…Research on graphene-based nanomaterials has boomed in biomaterial applications over the past few years. With outstanding physical, chemical and biological properties, graphene is considered to be revolutionary material and shows great potential for applications in tissue regeneration, drug delivery and other biomedical areas (Hu et al, 2020;Fu et al, 2021;Unal et al, 2021). Therefore, the purpose of this review is to highlight the scientific progress over the years and further summarize the physical and chemical properties, family members and applications in bone tissue engineering of this graphene-based nanomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, in terms of application, a sensitive detection method for H 2 O 2 , glucose, and AA was developed with the optimized Cu-NC-700 SAzymes. Hongye FeÀ SSN [14] Fe [15] RuÀ AlaÀ C 3 N 4 [16] AÀ CoÀ NG [17] FeÀ NÀ C [18] Apt/FeÀ NÀ C [19] FeÀ NÀ C [20] Pt/NiCo-LDH [21] FeÀ NÀ C [22] CoÀ MoS 2 [23] FeÀ N/C [24] CoÀ NÀ C [25] Biomedical therapy Cancer…”
Section: Wet Chemical Synthesismentioning
confidence: 99%
“…Although several nanomaterials have been reported for the electrochemical detection of UA, such as Prussian blue (PB)/nitrogen-doped carbon nanotubes (CNTs) [80] and gold nanoparticles loaded on graphene oxide (GO), [81] the defect of the low active site leads to their poor sensing performance to achieve high sensitivity, which is solved by the highly dispersed active sites of SAzymes. Fang Xinyu et al [17] reported a uric acid bionanosensing detection system (AÀ CoÀ NG) designed with cobalt-based SAzymes, whose principle reaction is: oxidation of Co generates Co 3 + À OH À . The redox reaction provides the conditions for electrochemical sensing, and the cobalt atoms of this experimental design are densely distributed in the The SAzymes system (AÀ CoÀ NG) with N-doped graphene body that has high enzyme-like electron sensing activity.…”
Section: Uric Acid and Dopamine Sensingmentioning
confidence: 99%
“…However, the thermodynamically unstable nature of single metal atoms poses challenges for preparing stable SACs. To successfully engineer SACs, suitable precursors (including metal and supporting materials), effective synthetic strategies and intriguing metalsupport interactions are three important considerations, which are also intimately correlated with the exotic geometric and electronic structures of SACs [22,24,25]. As a representative, Mn single-atom catalysts (Mn SACs) with Mn δ+ -N x sites have been developed and proved to be highly active for CO 2 reduction and oxygen reduction; however, they have seldom been explored for NRR [26][27][28][29][30].…”
Section: Mnmentioning
confidence: 99%